Cecilie Vindal Ødegaard, Juan Javier Rivera Andía, eds. 2019. Indigenous life projects and extractivism. Ethnographies from South America - Alcida Rita Ramos (América Crítica, 2020)
Book review of Cecilie Vindal Ødegaard, Juan Javier Rivera Andía, eds, Indigenous life projects and extractivism. Ethnographies from South America. Cham, Switzerland: Palgrave Macmillan, 2019, pp. 282.